Spectroscopic and magnetic properties of a Ni(II) complex with citric acid - Bovi Mitre, M. G. (2000)
The complex compound K₂[Ni(cit)(H₂O)₂]₂·4H₂O (cit = triionized citrate ion) seems to be a good model for the investigation of Ni(II)/citrate interactions that are of interest in relation to nickel metabolism and bioaccumulation. Its infrared and Raman spectra were recorded and analyzed on the basis of its structural peculiarities. The magnetic susceptibility, investigated in the temperature range between 1.9 and 300 K, shows the absence of magnetic interactions between the two metal centers present in this structure.